Minireview: Transcriptional Regulation of Adrenocortical Development - Hammer, Gary D.; Parker, Keith L.; Schimmer, Bernard P. (Endocrinology (Philadelphia), 2005)
The adrenal glands are comprised of two distinct endocrine organs: the outer cortex, which is derived from mesoderm and synthesizes steroid hormones, and the inner medulla, which contains neuroectodermal cells derived from the neural crest and produces the catecholamine hormones norepinephrine and epinephrine. The developmental program that gives rise to the adrenal gland begins early during embryogenesis and continues throughout gestation and well after birth. In this article, we review the molecular mechanisms of adrenal differentiation and development, focusing on the contributions of genes responsible for the development of the adrenal cortex as identified from studies of experimental animal models and human subjects with clinical diseases. These studies identify a hierarchical network of transcription factors, including Wilms’ tumor-1, steroidogenic factor-1, dosage-sensitive sex reversal, adrenal hypoplasia congenita, X-linked-1, PBX1, and CITED2, that both give rise to the adrenal cortex and subsequently determine its subsequent function in steroidogenesis.